Anti-Critical Race Theory Movement in Postsecondary Education: Faculty Expectations Confronting Emotionalities of Whiteness - Daniel D. Liou; Raquel Alvara (Ali Khorsandi Taskoh, 2021)
This self-narrativization study investigates two university faculty members' perceptions of their online classroom in the context of the anti-critical race theory (CRT) policies in the United States. After one semester of data collection and analysis, three thematic narratives emerged showing faculty perceptions of online students' behaviors in a graduate course where anti-CRT sentiments had an influence on student learning: (1) Sense of white victimhood; (2) Race deflections, control, and emotional detour, and (3) Faculty response to students' ideological echo chambers. Faculty perceptions suggest that these patterns of online learning were the consequence of emotionalities of whiteness, where White anti-CRT students actively resisted the course curriculum in an effort to default into an emotional state of race-neutrality, reinforcing the racial contract as the basis for their preparation as future PK-12 school principals. Leaders of postsecondary education must confront the emotionalities of whiteness. Inactions to stand firm on antiracism can embolden racism deniers to weaponize CRT to arbitrarily stop intellectual pursuits related to social injustices.